Comparative Phylogeography in the Taiwan–Luzon Volcanic Belt Indicates Fast Diversification History of Pachyrhynchus Weevils (Coleoptera: Curculionidae). Issue 6 (30th December 2022) - Ye, Yan-Jhih; Huang, Jen-Pan; Nguyen, Hung N; Villanueva, Reagan Joseph T; Amarga, Ace Kevin S; Tseng, Hui-Yun
Abstract: Geological isolation with limited gene flow can shape phenotypic diversification among different populations or species. From Luzon northward to Taiwan lies a series of isolated volcanic islands (the Taiwan–Luzon volcanic belt) where three Pachyrhynchus species [P. sarcitis (Behrens, 1887 ), P. nobilis (Heller, 1912 ) and P. semperi (Heller, 1912 )] (Coleoptera: Curculionidae: Entiminae: Pachyrhynchini) are sympatrically distributed. With intraspecific color variation across different islands, these three weevil species provide a unique opportunity to study genetic divergence associated with geographic isolation and/or phenotypic differences. In this study, genome-wide single nucleotide polymorphism (SNP) data derived from ddRAD-seq was used to reconstruct the speciation history and to delimit species within each of the three species. Our results indicate all three species have ancient diversification histories in southern islands of the Taiwan–Luzon volcanic belt instead of more recent diversification histories in northern islands. Ancestral effective population size estimations also support a scenario of a series of founder colonization events from southern to northern islands in the volcanic belt. Most island populations are monophyletic, and early-divergent populations with deep genetic structures are supported statistically as distinct species. However, color variations could occur between populations with very recent diversification, indicating a fast-evolving rate in the change of coloration, possibly due to müllerian mimicry or founder effects across this region.